Gender as a Moderator of the Influence Entrepreneurial Education and Entrepreneurial Characteristics on Entrepreneurial Intention - Kusmintarti, Anik; Ismanu, Sidik; Indah Riwajanti, Nur (International Journal of Engineering and Technology, 2018)
The Indonesian government continuously strives to increase the number of entrepreneurs, and universities are expected to play an active role in fostering entrepreneurial spirit among students. This study was aimed to analyze the role of gender as a moderator of entrepreneurial education influence and entrepreneurial characteristics on entrepreneurial intention. Population of the study was the students  of the State Polytechnic of Malang who have involved in the Student Entrepreneurial Program in 2015 and 2016. The study used judgment sampling technique to select the respondent and the data collected through questionnaires distribution. Data analysis used descriptive statistics and moderation regression analysis. The results of study show that gender does not moderate the influence of entrepreneurial education and entrepreneurial characteristics on entrepreneurial intention. The result can be interpreted as nothing difference in the intention of opening new business in the future for male and female students who have followed entrepreneurship lecture, entrepreneurship seminar, entrepreneurship expo, and business practices. Furthermore, there is not difference in the motivation of opening new business in the future for male and female students who have  characteristics : self-efficacy, need for achievement and social networking. Self-efficacy contributed the highest in supporting the entrepreneurial characteristics.